Phylogenetic analysis linked fatal neurologic disease in leopards (Panthera pardus) to Asia-5 lineage of canine distemper virus in Nepal - Amir Sadaula; Prajwol Manandhar; Bijaya Kumar Shrestha; Parbat Jung Thapa; Suresh Nepali; Janardan Dev Joshi; Babu Ram Lamichhane; Rachana Shah; Madhu Chetri; Kiran Raj Rijal; Kamal Prasad Gairhe; Naresh Subedi; et al. (Virus Research)
Canine distemper virus (CDV) is responsible for a highly contagious and often fatal neurological disease that affects various carnivores, including domestic dogs. In Nepal, recent reports of CDV exposure and illness in leopards (Panthera pardus) have raised concerns about the transmission of the virus among domestic dogs and wild carnivores. To investigate the genetic lineage and spread of CDV, our study utilized archived post-mortem samples from four leopards that exhibited clinical signs suggestive of canine distemper infection. These leopards were rescued in the Palpa, Dolakha, Kathmandu, and Parbat districts. Our phylogenetic analysis revealed that the CDV strains circulating among the leopards belong to the Asia-5 lineage, which is also prevalent among dogs and wild carnivores in Nepal and neighboring India. The genetic relatedness between the leopard CDV sequences and those from both dogs and other carnivores within the Asia-5 lineage suggests that leopards in Nepal may have acquired the virus from multiple sources, potentially facilitated by their generalist dietary habits preying on dogs and even mesocarnivores. Furthermore, we inspected specific amino acid substitution in the hemagglutinin gene of leopard CDV, which also suggests possible transmission from both domestic dogs and non-canid hosts, although further research is needed to draw definitive conclusions. Given the vulnerable state of the leopard population in Nepal, already threatened by poaching and retaliatory killing, the emergence of CDV as a potential novel threat is deeply concerning. Comprehensive surveillance studies are essential to understand the dynamics of CDV spillover and to develop informed interventions. Urgent measures, including vaccination programs and effective control of the dog population, are needed to mitigate the impact of this disease and safeguard the future of Nepal's leopards and other wild carnivores.